The order Plecoptera (Insecta) of Nariño department, Colombia - Castillo, Guillermo; Zúñiga, María del Carmen; Bacca, Tito (Revista Colombiana de Entomología, 2013)
The Plecoptera of Nariño are represented by Anacroneuria (Perlidae) and Claudioperla (Gripoterygidae). The only species recorded for Nariño are A. planada and A. tejon. Considering the lack of studies of Plecoptera in this region, the objective of this work was to carry out an inventory of the order for the department. We documented thirteen Anacroneuria species, with emphasis on the Andean region; eleven of these species aare newly recorded in this region: A. anchicaya, A. cordillera, A. choco, A. citara, A. farallonensis, A. jewetti, A. munchique, A. portilla, A. quilla, A. socapa and A. tatama. Additional information on the distribution and ecology of the species is presented; they represent 21.3% of the known species for Colombia.